Immigration reform : proposals and projections - Ross, Molloy C. (Immigration in the 21st century: political, social and economic issues., 2013)
For several years, some Members of Congress have favored ""comprehensive immigration reform"" (CIR), a label that commonly refers to omnibus legislation that includes increased border security and immigration enforcement, expanded employment eligibility verification, revision of nonimmigrant visas and legal permanent immigration, and legalization for some unauthorized aliens residing in the country. Leaders in both chambers have identified immigration as a legislative priority in the 113th Congress. While Members of the House reportedly have considered several different approaches to immigrati.